Novel lanthanide borate nano-material with controllable morphology and preparation method of novel lanthanide borate nano-material

The preparation of lanthanide borate nanomaterials by adjusting reaction conditions was solved, and the problems of high synthesis cost and difficulty in morphology control of lanthanide borate nanomaterials were solved, and controllable and stable preparation was achieved, and new application prospects were opened.

CN119660758APending Publication Date: 2025-03-21浙江工业大学绍兴研究院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411804442.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The synthesis and morphological control of lanthanide borate nanomaterials usually require high costs and time, and it is difficult to achieve stable preparation and morphological control.

Method used

By adjusting reaction conditions, such as temperature, precursor species and concentration, and reaction time, the lanthanide borate nanomaterials are prepared by hydrothermal method to form lanthanide borate nanoparticles, nanoparticle agglomerates, nanorods, nanofibers and three-dimensional networks.

Benefits of technology

The stable preparation of lanthanide borate nanomaterials with controllable morphology has been achieved, which reduces costs, simplifies the process flow, and opens up new application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660758A_ABST
    Figure CN119660758A_ABST
Patent Text Reader

Abstract

The invention discloses a novel lanthanide borate nano-material with controllable morphology and a preparation method thereof. The technical problems that the synthesis cost of the lanthanide borate nano-material is high and the morphology is difficult to control are solved through a simple hydrothermal method. Compared with other methods, the synthetic method of the lanthanide borate nano material is simple to operate, stable in product and low in cost, lanthanide borate nano materials with a series of morphologies such as nano particles, nano particle aggregates, nano rods, nano fibers and three-dimensional networks can be prepared by controlling conditions such as temperature and precursors, and synthesis is stable and easy to control. The lanthanide borate nano-material prepared by the method has a crystal structure which is not found by other lanthanide borate nano-materials, and has application prospects in the fields of plant epidemic disease prevention and control, semiconductors, catalysis, energy sources and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of nano materials, and in particular to a novel lanthanum borate nano material with controllable morphology and a preparation method thereof. Background Art

[0002] Lanthanum borate nanomaterials play an important role in many fields due to their unique physical and chemical properties. In addition to their applications in plant disease prevention, semiconductors, catalysis, energy and other fields, lanthanum borate nanomaterials also exhibit good physical and chemical properties such as optics, electricity, magnetism and ferroelectricity, which makes them have broad prospects in the application fields of luminescent materials, photocatalytic materials, solid electrolytes and so on.

[0003] However, the synthesis and morphology control of lanthanide borate nanomaterials usually require high costs and time, and it is difficult to achieve stable preparation and morphology control. Traditional synthesis methods, such as high-temperature solid-phase method and sol-gel method, often require high-temperature reactions in high-temperature furnaces with atmosphere requirements, resulting in reaction products that are usually uneven in size and poor in performance. The materials can usually only reach the micron level and are difficult to reduce further.

[0004] Therefore, it is necessary to develop a new method to prepare lanthanide borate nanomaterials with controllable morphology through a simple approach. Summary of the invention

[0005] In view of the problems existing in the prior art, the first object of the present invention is to provide a novel lanthanide borate nanomaterial with controllable morphology. This lanthanide borate nanomaterial can be formed into lanthanide borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks by adjusting the reaction conditions during preparation, and has high morphology controllability and preparation stability. In addition, this lanthanide borate nanomaterial with a crystal structure has not been discovered in the past and has certain application prospects in various fields.

[0006] A new type of lanthanum borate nanomaterial with controllable morphology can form lanthanum borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks by adjusting the reaction conditions during preparation, wherein the reaction conditions are temperature, precursor type, precursor concentration and reaction time; the new type of lanthanum borate nanomaterial has a crystal structure not found in other lanthanum borate nanomaterials, and the XRD diffraction pattern of its crystal structure has obvious diffraction peaks near 26° and 30°, and weaker diffraction peaks near 20°, 22°, 24°, 28°, 33°, 45°, 47° and 53°, and lattice fringes matching the diffraction pattern can be observed under a high-resolution transmission electron microscope. The crystal structure is not the same as that found in the currently disclosed lanthanum borate materials, and is a new type of lanthanum borate nanomaterial.

[0007] Preferably, the novel morphology-controllable lanthanide borate nanomaterial comprises a lanthanide metal element and a borate ion, and the molar ratio of the lanthanide metal element to the borate ion is (1-3):1.

[0008] The morphology control method of the above-mentioned novel lanthanide borate nanomaterial is: forming lanthanide borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks by adjusting the reaction conditions. Specifically, nanoparticles will be formed at a relatively low temperature, precursor concentration and reaction time, and as the conditions are improved, the morphology of nanoparticles to nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks will begin to change. For example, nanoparticles are formed by reaction at a relatively low temperature, nanoparticle aggregates are prepared by increasing the reaction temperature, and nanorods are prepared by further increasing the temperature.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned novel lanthanide borate nanomaterial with controllable morphology, comprising the following steps: Step (1): preparing a lanthanide metal salt solution of a certain concentration, denoted as solution A; preparing a mixed solution of boric acid and an inducer in a certain proportion, denoted as solution B, and adding solution B dropwise into solution A under stirring to form a uniform liquid; Step (2): adding the homogeneous liquid obtained in step (1) into a reactor for hydrothermal reaction, and cooling naturally after the reaction is completed; Step (3): The obtained white liquid is washed by centrifugation with deionized water to remove unreacted precursors, thereby obtaining a novel lanthanum borate nanomaterial with controllable morphology.

[0010] Preferably, the lanthanide metal salt in step (1) comprises one of lanthanide acetate, nitrate, sulfate, hydrochloride, bromide and iodide.

[0011] Preferably, the lanthanide metal element is one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium. Preferably, the concentration of the metal salt in step (1) is 0.005-0.3 mM.

[0012] Preferably, the reaction temperature is 80-180°C.

[0013] Preferably, the induction liquid in step (2) comprises one of ammonia water, sodium hydroxide and potassium hydroxide. The hydroxide ions in the induction agent can control the hydrolysis rate of boric acid and chelate with lanthanide metal ions to control the direction of material growth at different temperatures, thereby forming borate materials with different morphologies.

[0014] Therefore, the present invention has the following beneficial effects: The present invention solves the technical problems of high synthesis cost and difficult morphology control of lanthanide borate nanomaterials through a simple hydrothermal method. First, compared with other methods, this method for synthesizing lanthanide borate nanomaterials can prepare lanthanide borate nanomaterials with a series of morphologies such as nanoparticles, nanoparticle agglomerates, nanorods, nanofibers and three-dimensional networks by controlling conditions such as temperature and precursors, and the synthesis is stable and easy to control. Secondly, compared with other methods, this method is simple to operate, has stable products and low cost. Finally, the lanthanide borate nanomaterials prepared by this method have a crystal structure that has not been found in other lanthanide borate nanomaterials, and may have application prospects in the fields of plant disease prevention and control, semiconductors, catalysis, energy, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the XRD diagram of the lanthanum borate nanomaterial in Example 1.

[0016] Figure 2 TEM images of lanthanum borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks in Example 1.

[0017] Figure 3 This is the XRD diagram of the samarium borate nanomaterial in Example 2.

[0018] Figure 4 TEM images of samarium borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks in Example 2.

[0019] Figure 5 This is an XRD comparison chart of the lanthanum borate nanomaterial in Example 1, the samarium borate nanomaterial in Example 2, and the praseodymium borate nanomaterial in Example 3.

[0020] Figure 6 This is the HRTEM image of the praseodymium borate nanomaterial in Example 3.

[0021] Figure 7 TEM images of praseodymium borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks in Example 3. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0023] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1

[0024] 3 mmol (1.29 g) of lanthanum nitrate hexahydrate was added to 10 mL of deionized water and stirred for 0.5 h until completely dissolved. Then 3 mmol (0.185 g) of boric acid and 0.4 mL of ammonia water were added to another 10 mL of deionized water and stirred for 0.5 h until completely dissolved. Then the mixed solution of boric acid and ammonia water was added dropwise to the lanthanum nitrate solution and stirred for 2 h to obtain a clear and transparent white solution. Subsequently, the above liquid was added to a 25 mL polytetrafluoroethylene liner, placed in a matching stainless steel jacket and tightened. Then the hydrothermal autoclave was placed in a forced air drying oven and reacted at 80 °C for 12 h. After the reaction was completed, the temperature was naturally lowered, and the obtained white liquid was centrifuged and washed 5 times with deionized water (8000 rpm). The final product was dissolved in deionized water to obtain a lanthanum borate nanoparticle solution.

[0025] By changing the reaction temperature to 100°C, 120°C, 150°C, and 180°C, lanthanum borate nanoparticle aggregates, nanorods, nanofibers, and three-dimensional networks can be obtained, respectively.

[0026] Figure 1 This is the XRD diagram of the lanthanum borate nanomaterial in Example 1. The corresponding crystal structure cannot be found in databases such as ICDD and ICSD.

[0027] Figure 2 TEM images of lanthanum borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks in Example 1. By increasing the temperature, the material changes from nanoparticles to nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks. Example 2

[0028] 0.05 mmol (0.164 g) of samarium acetate was added to 10 mL of deionized water and stirred for 0.5 h until completely dissolved. Then 3 mmol (0.185 g) of boric acid and 0.4 mL of sodium hydroxide were added to another 10 mL of deionized water and stirred for 0.5 h until completely dissolved. Then the mixed solution of boric acid and sodium hydroxide was added dropwise to the samarium acetate solution and stirred for 2 h to obtain a clear and transparent white solution. Subsequently, the above liquid was added to a 25 mL polytetrafluoroethylene liner, placed in a matching stainless steel jacket and tightened. Then the hydrothermal autoclave was placed in a forced air drying oven and reacted at 80 °C for 12 h. After the reaction was completed, the temperature was naturally lowered, and the obtained white liquid was centrifuged and washed 5 times with deionized water (8000 rpm). The final product was dissolved in deionized water to obtain a samarium borate nanoparticle solution.

[0029] By changing the amount of samarium acetate added to 0.246 g, 0.328 g, 0.496 g, and 0.992 g, samarium borate nanoparticle agglomerates, nanorods, nanofibers, and three-dimensional networks can be obtained, respectively.

[0030] Figure 3 This is the XRD pattern of the samarium borate nanomaterial in Example 2. Its crystal structure is consistent with the lanthanum borate nanomaterial in Example 1, and the corresponding crystal structure cannot be found in databases such as ICDD and ICSD.

[0031] Figure 4 The transmission electron microscope images of samarium borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks in Example 2. By increasing the amount of precursor added, the material changes from nanoparticles to nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks. Example 3

[0032] 3 mmol (1.29 g) of praseodymium nitrate hexahydrate was added to 10 mL of deionized water and stirred for 0.5 h until completely dissolved. Then 3 mmol (0.185 g) of boric acid and 0.1 mL of ammonia water were added to another 10 mL of deionized water and stirred for 0.5 h until completely dissolved. Then the mixed solution of boric acid and ammonia water was added dropwise to the praseodymium nitrate solution and stirred for 2 h to obtain a clear and transparent white solution. Subsequently, the above liquid was added to a 25 mL polytetrafluoroethylene liner, placed in a matching stainless steel jacket and tightened. Then the hydrothermal autoclave was placed in a forced air drying oven and reacted at 80 °C for 12 h. After the reaction was completed, the temperature was naturally lowered, and the obtained white liquid was centrifuged and washed 5 times with deionized water (8000 rpm). The final product was dissolved in deionized water to obtain a praseodymium borate nanoparticle solution.

[0033] By changing the amount of ammonia added to 0.2 mL, 0.3 mL, 0.4 mL, and 0.5 mL, praseodymium borate nanoparticle aggregates, nanorods, nanofibers, and three-dimensional networks can be obtained, respectively.

[0034] Figure 5 The XRD comparison diagrams of the lanthanum borate nanomaterial in Example 1, the samarium borate nanomaterial in Example 2, and the praseodymium borate nanomaterial in Example 3 are shown. It can be seen that the lanthanum borate nanomaterials prepared by this method are all of this crystal structure, and the XRD diffraction pattern of the crystal structure has obvious diffraction peaks near 26° and 30°, and weaker diffraction peaks near 20°, 22°, 24°, 28°, 33°, 45°, 47° and 53°. Lattice fringes matching the diffraction pattern can be observed under a high-resolution transmission electron microscope. The corresponding standard crystal structure cannot be found in databases such as ICDD and ICSD.

[0035] Figure 6This is the HRTEM image of the praseodymium borate nanomaterial in Example 3, where lattice fringes can be observed.

[0036] Figure 7 The transmission electron microscope images of praseodymium borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks in Example 3. By increasing the amount of ammonia water added as an inducer, the material changes from nanoparticles to nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks.

[0037] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A novel lanthanide borate nanomaterial with controllable morphology, wherein the controllable morphology includes at least from nanoparticles to three-dimensional networks; characterized in that: The novel lanthanum borate nanomaterial has a crystal structure not found in other lanthanum borate nanomaterials; the novel lanthanum borate nanomaterial contains lanthanum metal elements and borate, and the molar ratio of the two is (1-3):

1.

2. A novel lanthanide borate nanomaterial with controllable morphology according to claim 1, characterized in that: Lanthanide borate nanoparticles, nanoparticle aggregates, nanorods, nanofibers and three-dimensional networks can be formed by adjusting the reaction conditions during preparation.

3. The novel lanthanide borate nanomaterial with controllable morphology according to claim 2, characterized in that: The reaction conditions include temperature, precursor type, precursor concentration, and reaction time.

4. The novel lanthanum borate nanomaterial with controllable morphology according to claim 1, characterized in that: The XRD diffraction pattern of the crystal structure has obvious diffraction peaks near 26° and 30°, and weaker diffraction peaks near 20°, 22°, 24°, 28°, 33°, 45°, 47° and 53°, and lattice fringes matching the diffraction pattern can be observed under a high-resolution transmission electron microscope.

5. A method for preparing a novel morphology-controllable lanthanide borate nanomaterial according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step (1): preparing a lanthanide metal salt solution of a certain concentration, denoted as solution A; A mixed solution of boric acid and an inducer in a certain ratio is prepared, which is referred to as solution B. Solution B is added dropwise into solution A under stirring to form a uniform liquid; Step (2): adding the homogeneous liquid obtained in step (1) into a reactor for hydrothermal reaction, and cooling naturally after the reaction is completed; Step (3): The obtained white liquid is washed by centrifugation with deionized water to remove unreacted precursors, thereby obtaining a novel lanthanum borate nanomaterial with controllable morphology.

6. The method for preparing a novel lanthanide metal salt nanomaterial with controllable morphology according to claim 5, characterized in that: The lanthanide metal element is one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.

7. The method for preparing a novel lanthanide borate nanomaterial with controllable morphology according to claim 5, characterized in that: The anion in the lanthanide metal salt solution in step (1) includes one of nitrate ion, acetate, sulfate, hydrochloride, bromide, and iodide.

8. The method for preparing a novel lanthanide borate nanomaterial with controllable morphology according to claim 5, characterized in that: The concentration of the metal salt in step (1) is 0.001-1 mM; preferably, the concentration of the metal salt is 0.005-0.3 mM.

9. The method for preparing a novel lanthanide borate nanomaterial with controllable morphology according to claim 5, characterized in that: In step (1), the inducing agent is one of ammonia water, sodium hydroxide and potassium hydroxide.

10. The method for preparing a novel lanthanide borate nanomaterial with controllable morphology according to claim 5, characterized in that: The hydrothermal reaction time of step (2) is 2-12 hours, and the reaction temperature is 60-250°C; preferably, the reaction temperature is 80-180°C.